(untitled) (Eurasian Journal of Ecology, 2019)
The article presents the results of monitoring studies in the field of agriculture, the results on waterphysical, chemical, and mechanical properties of the soil. The role of soil in the human economy is huge. Soil – a critical component of all terrestrial biota and biosphere of the Earth as a whole, through the soil cover of the Earth are numerous ecological relationships of all living on earth and in the land of organisms (including humans) with the lithosphere, hydrosphere and atmosphere. The role of soil in the human economy is huge. The study of soil is necessary not only for agricultural purposes, but also for the development of forestry, engineering and construction business, of health problems, exploration and mining operations, the organization of green areas in the urban economy, environmental monitoring and so on.Consequently, the soil needs to systematically monitor, to monitor their condition, especially in the agricultural sector, because every year there is depletion of soil humus cover. Key words: soil, soil fertility, soil density, monitoring